2016
DOI: 10.4028/www.scientific.net/kem.678.50
|View full text |Cite
|
Sign up to set email alerts
|

Straw Based Materials for Building Retrofitting and Energy Efficiency

Abstract: This work aimed to measure the hygrothermal properties of some different straw-based mix that could be used as building materials (panels or bricks). Straw is used to improve the hygrothermal performances of the final products. Several mix were produced adding different percentages of straw. Two types of fibers were used: wheat straw and bean straw. The results indicated that increasing the percentages of straw greater effects on the change of thermal properties can be appreciated. Furthermore the results also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To compare the thermal conductivities of the straw boards with those of other straw bio-based materials and investigate the applicability of the fitting formula, the data scatters for the λ of straw bales and composites from the previous studies [4,8,9,13,15,25,28] are shown in Figure 8 versus ρ. As stated in the Introduction, the densities of straw bales and composites in previous studies are within a small range.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the thermal conductivities of the straw boards with those of other straw bio-based materials and investigate the applicability of the fitting formula, the data scatters for the λ of straw bales and composites from the previous studies [4,8,9,13,15,25,28] are shown in Figure 8 versus ρ. As stated in the Introduction, the densities of straw bales and composites in previous studies are within a small range.…”
Section: Discussionmentioning
confidence: 99%
“…The composites with sodium silicate demonstrated the highest resistance, avoiding mold growth at high relative humidity levels. Besides its several benefits, it has also shown some drawbacks, such as high hygroscopicity and low moisture resistance [45,48], which could cause the degradation of the materials [49]. Furthermore, it could be less eco-efficient than other adhesives (i.e., bio-based ones or natural glues).…”
Section: Introductionmentioning
confidence: 99%